2005
DOI: 10.1089/end.2005.19.441
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic Partial Nephrectomy: The NYU Technique

Abstract: The introduction of the daVinci surgical system has changed the way both surgeon and patient view radical prostatectomy. We hypothesized that the same theoretical and tangible benefits may be realized when employing the system for partial nephrectomy. This paper reviews our technique of robot-assisted laparoscopic partial nephrectomy (RALPN) utilizing the daVinci surgical system. Intraoperative hilar clamping is utilized in all cases. With the daVinci system, the tumor is excised with cold scissors, biopsies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 8 publications
7
77
0
Order By: Relevance
“…7 RPN is suitable for intracorporeal suturing with the use of an endo-wrist instrument. 8 To date, numerous preliminary studies on RPN have shown that this technique is comparable to LPN. 9 Although one recent report on the outcomes of RPN compared with OPN has been promising, 10 there are almost no studies that have compared RPN with OPN.…”
Section: Introductionmentioning
confidence: 99%
“…7 RPN is suitable for intracorporeal suturing with the use of an endo-wrist instrument. 8 To date, numerous preliminary studies on RPN have shown that this technique is comparable to LPN. 9 Although one recent report on the outcomes of RPN compared with OPN has been promising, 10 there are almost no studies that have compared RPN with OPN.…”
Section: Introductionmentioning
confidence: 99%
“…RPN is a viable alternative of more technical challenging LPN, since the da Vinci robot system has advantages such as the seven degree of freedom, high definition imaging, easily movement, stable motion for tremor, resection and suturing can be performed easier and faster (18). Disadvantages of robotic surgery are lack of tactile feedback, high cost, and time consumed for the setting up the robot (19). Moreover, the surgeon is unscrubbed in the operation console and thus could not proceed to the operating table immediately in an emergent situation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Represented are 5 case series and a single case report. Furthermore, conversion rates of 25% and 20% in the reports by Phillips and colleagues 69 and Caruso and colleagues 70 highlight the steep early learning curve with this procedure. More convincing studies demonstrating the superiority of RALPN over conventional laparoscopic techniques are needed before RALPN can be adopted routinely.…”
Section: Partial Nephrectomymentioning
confidence: 96%